Effectiveness of adjunctive screening tools for potentially malignant oral disorders and oral cancer: A systematic review - Khalid Zabin Alotaibi; Shaul Hameed Kolarkodi (Elsevier, 2024)
Background and objectives: To enhance the abilities of healthcare professionals to make informed treatment decisions and establish accurate diagnoses, it is essential to assess the diagnostic reliability of different adjunctive aids. This systematic review aimed to compare the accuracy of various adjunctive methods for diagnosing suspected oral cancer (OC) or potentially malignant oral disorders (OPMD) in adults against histopathological investigative results. Materials and methods: The review protocol registered in the PROSPERO database (CRD42023463525) was developed in strict accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analysis-Diagnostic Test Accuracy checklist. A comprehensive electronic search was conducted to identify relevant research articles published between January 2014 and April 2023 using the PubMed and EBSCO databases. The research question was meticulously structured following the participants' index test, reference standard, target condition, and study setting framework. To evaluate methodological quality and assess the risk of bias (RoB), the Quality Assessment for Diagnostic Accuracy Studies-2 tool was used. Results: An initial search yielded 483 publications, which were reduced to 278 after removal of duplicates. Finally, 85 publications underwent full-text review by two investigators, which lead to 29 studies that met the inclusion criteria. Among these, 7% had a low RoB, 72% had an unclear RoB, and 21% had a high RoB. Applicability concerns were expressed in 59% of the studies with low concern, 31% with unclear quality evidence of concern, and 10% with high concern. Conclusion: The review findings support the use of these diagnostic methods as valuable adjuncts to biopsy for the early detection of various OPMD and OC. They also highlight the importance of regular screening and awareness in reducing the global burden of OC, while acknowledging that they cannot replace the gold standards of surgical biopsy and histopathological evaluation.